Broad thermal spectrum metagenomic laccase with action for dye decolorization and fentin hydroxide treatment - Lima, Natália Sarmanho Monteiro [UNESP]; Gomes-Pepe, Elisângela Soares [UNESP]; Campanharo, João Carlos [UNESP]; de Macedo Lemos, Eliana Gertrudes [UNESP] (Springer Nature, 2022)
Laccases are multicopper oxidases that act on various phenolic and non-phenolic compounds, enabling numerous applications including xenobiotic bioremediation, biofuel production, drug development, and cosmetic production, and they can be used as additives in the textile and food industries. This wide range of uses makes these enzymes extremely attractive for novel biotechnology applications. Here, we undertook the kinetic characterization of LacMeta, a predicted as homotrimeric (~ 107,93 kDa) small laccase, and demonstrated that this enzyme performs best at an acidic pH (pH 3–5) towards ABTS as substrate and has a broad thermal spectrum (10–60 °C), which can promote high plastic action potential through dynamic environmental temperature fluctuations. This enzyme showed following kinetic parameters: kcat = 6.377 s−1 ± 0.303, Km = 4.219 mM, and Vmax = 24.43 µM/min (against ABTS as substrate). LacMeta almost completely degraded malachite green (50 mg/mL) in only 2 h. Moreover, the enzyme was able to degrade seven dyes from four distinct classes and it respectively achieved 85% and 83% decolorization of methylene blue and trypan blue with ABTS as the mediator. In addition, LacMeta showed potential for the degradation of two thirds of an agricultural fungicide: fentin hydroxide, thus demonstrating its biotechnological aptitude for bioremediation. The results of this study suggest that LacMeta has potential in textile wastewater treatment and that it could help in the bioremediation of other human/environmental toxins such as pesticides and antibiotic compounds belonging to the same chemical classes as the degraded dyes. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Bioremediation; Dyes; Laccase; Metagenomics